Arkeologiska undersökningar av järnhanteringsplatser i Tvååkersområdet - Strömberg, Bo (Hikuin, 2004)
The archaeological investigations at Tvååker in Halland By Strömberg The first archaeological investigations at Tvååker were undertaken in the 1920s by Carl Sahlin and John Nihlén. They were focusing on the small rapids at Järnmölle farm, but did not find any remains of iron production on the site. Nihlén discovered, however, some furnaces at Högsryd nearby and a slag heap at Järnvirke. Another archaeological survey was not undertaken until 1987, when yet another seven sites of iron production sites were registrated and described, among them the site at Ugglehult/Dövared. When the project started in 1993 one of the important issues was to investigate whether any slag could be found at Järnmölle, in order to determine if this could be the site of the iron mill mentioned in the medieval documents. However, no slag was found in situ, which led to the conclusion that the iron mill had been situated elsewhere. Södra Järnvirke and Järnvirke were other sites of interest At Södra Järnvirke a slag heap measuring 9×4 meters and 0,8 meter height had been discovered in 1987, When excavated, a pair of bloomery furnaces were found along its south east side. Constructed with slag tapping, they were similar to the bloomery furnaces that have been found in Västergötland dating from the 11th and 12th centuries and coherent with the radiocarbon dating at Södra Järnvirke, The largest slag heap, measuring 22×9 meters and 1 meter in height, was situated in the vicinity of Järnvirke. The analysis of the slag and the burned clay from the furnace inclining showed that the furnaces there had been of the same type. The largest archaeological excavation was undertaken at the Ugglehult/Dövared site. Between a narrow road on the west side and a low stone wall on the east side the site is situated by the rapids of the Sanda stream. The stone wall is indicated on a map from 1727. Here a large slag heap, a pond and a pond wall, the remains of a mill as well as a smithy with three hearths and the foundations of a water wheel in the rapids were found. The radiocarbon analysis dated the iron production to the 11th to the 12th century. In the beginning of the 14th century a (flour) mill was founded in the same place and the pond wall was rebuilt into a higher construction. A 7×6 meter building with its contents on the shore of the rapids together with the majority of the slags proved that hearths had been used for bloomery iron production and that bellows had been powered with a water wheel. A lot of smithing slag and hammer scale that was spread over the site, showed that a forge also had been part of the production unit. This water powered smithy is, as far as wee know, the oldest known and exavated site of its kind in Europe. Probably far from being the only one of its kind at the time, we can only hope that water powered iron production sites would be found in for instance Germany, France or Italy. This would make a better understanding possible of one of the most important innovations in the history of metallurgy, the water wheel technology, A technology that opened up iron production for a world wide industrialisation.